Electronic bandgap miniaturized UWB antenna for near-field microwave investigation of skin - Alani, Sameer; Zakaria, Zahriladha; Saeidi, Tale; Ahmad, Asmala; Alsariera, Hussein; Al-Heety, Othman S.; Mahmood, Sarmad Nozad (American Institute of Physics Inc., 2021)
Near-field microwave investigation and tomography has many practical applications, especially where the trend of fields and signals in different environments is vital. This article shows an elliptical patch ultra-wideband antenna fed by a transmission line for the near-field characterization of cancerous cells in the skin. The antenna comprises an elliptical patch, stub loading to shift the band to lower bands, and an electronic bandgap structure on the ground side. Even though the antenna has a low profile of 15 × 15 mm2, the proposed antenna has more promising results than recent studies. Furthermore, both simulated near-field and far-field results show a broad bandwidth of 3.9–30 GHz and a resonance at 2.4 GHz applicable for industrial, scientific, and medical band applications. The proposed antenna also illustrates a peak gain of 6.48 dBi and a peak directivity of 7.09 dBi. Free space and skin (on a layer of breast fat and a tumor with a diameter of 4 mm at the boundary of skin and breast) are used as test environments during the simulation and measurement of near-field and far-field investigations while considering a phantom breast shape. Both far-field and near-field microwave investigations are performed in Computer Simulation Technology studio, and results are then compared with the measured data. The simulated and measured results are in good agreement, and the focused energy around the tumor is completely reconstructed. Therefore, the proposed antenna can be an adequate candidate for the differentiation of breast skin and tumor to reconstruct the tumor’s image.